2003
DOI: 10.1063/1.1600505
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 60-nm transistors on 4-in. wafer using nanoimprint at all lithography levels

Abstract: Nanoimprint lithography (NIL) is a paradigm-shift method that has shown sub-10-nm resolution, high throughput, and low cost. To make NIL a next-generation lithography tool to replace conventional lithography, one must demonstrate the needed overlay accuracy in multilayer NIL, large-area uniformity, and low defect density. Here, we present the fabrication of 60-nm channel metal–oxide–semiconductor field-effect transistors on whole 4-in. wafers using NIL at all lithography levels. The nanotransistors exhibit exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
76
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(77 citation statements)
references
References 7 publications
0
76
0
1
Order By: Relevance
“…Locating an individual point defect of the pointdefect array at a precise position within the self-assembled PC requires NIL with advanced aligning techniques. [32,33] Nevertheless, the relative position of these point defects can be easily controlled with our fabrication method. A method of simultaneously fabricating point and line defects into a self-assembled PC, of which the positions can be tuned precisely by mold design, can be immediately adopted following the work described here.…”
mentioning
confidence: 99%
“…Locating an individual point defect of the pointdefect array at a precise position within the self-assembled PC requires NIL with advanced aligning techniques. [32,33] Nevertheless, the relative position of these point defects can be easily controlled with our fabrication method. A method of simultaneously fabricating point and line defects into a self-assembled PC, of which the positions can be tuned precisely by mold design, can be immediately adopted following the work described here.…”
mentioning
confidence: 99%
“…Remarkable progress was made in 1995 when Chou et al demonstrated a nanostructure with 25 nm resolution obtained by nanoimprinting and subsequent pattern transfer [17,18]. Since then, nanoimprinting has attracted great attention for fabricating micro/nanostructures for various applications including magnetic [19,20], electronic [21,22], optical [23,24], and biological devices [25,26]. Based on thermal-NIL, alternative methods have also been demonstrated.…”
Section: Nilmentioning
confidence: 99%
“…Among the emerging techniques, nanoimprint lithography (NIL) clearly stands out as a promising technology for high-throughput and highresolution nanometer-scale patterning, [1,2] which can achieve resolutions beyond the limitations set by light diffraction or beam scattering that are encountered in other traditional techniques. Developments in this area have enjoyed great momentum in the past decade and numerous applications, such as in Si electronics, [3,4] organic electronics and photonics, [5,6] magnetics, [7,8] and biology [9][10][11][12] have been exploited by many researchers. On the other hand, the current process and throughput in NIL (on the order of a few minutes per wafer) is still far from meeting the demands of many practical applications, especially in photonics, biotechnology, and organic optoelectronics.…”
mentioning
confidence: 99%